Wiersze noworoczne Jarosława Iwaszkiewicza. Od poezji okolicznościowej do gatunku prywatnego - Romaniuk, Radosław (Załącznik Kulturoznawczy, 2024)
The author analyzes the poems by Jarosław Iwaszkiewicz written at the turn of the year, either the last day of the passing year or the first day of the new year. He distinguishes between the trend of occasional “New Year’s poems” and the trend of private poems. The latter includes texts whose manuscripts, preserved in the writer’s archive, bear a date capturing the moment of the turn of the year. The circumstances of their creation, common motifs, and the ritualistic nature of their composition, emphasized by the writer, suggest that he treated those texts as a private genre practiced by him. The texts attempts to characterize this genre.